Beyond Victims and Villains: Young People's Acts of Citizenship during Covid-19. (August 2022) - Estellés, Marta; Bodman, Holly; Mutch, Carol
During the Covid-19 crisis, stereotypical images of young people as selfish troublemakers or passive victims appeared in the media and scholarly publications. These persistent views disregard many young people's authentic experiences and civic contributions. In this article, we challenge these perceptions by highlighting young people's acts of citizenship during the pandemic lockdowns that took place during 2020 in Aotearoa New Zealand. Despite being internationally praised for its compliant Covid-19 response, citizens were prepared to challenges the pandemic restrictions in order to have their voices heard. Young people were often at the forefront of these protests, wanting to actively participate in matters that concerned them by joining Black Lives Matter marches or campaigning to lower the voting age. At the same time, young people engaged in more personal and invisible acts of citizenship within their families and school communities. In this article, we share evidence from our empirical study into young people's social and political engagement during the Covid-19 lockdowns in Aotearoa New Zealand. Implications of this study for citizenship education are discussed.